Translation Procedures of Disease Terms in the Glossary of Medicine, Technology, and Sport 2025 - Made Wira Afrian; Ni Made Verayanti Utami (Universitas Islam Negeri Palopo, 2026)
This study investigates the translation procedures applied to disease terminology within a non-narrative glossary environment, where terms are presented as isolated lexical entries without supporting sentence context. Disease terminology was selected because it presents distinctive translation challenges arising from lexical gaps, standardized international nomenclature, and culturally established vernacular equivalents. Using Peter Newmark's taxonomy of translation procedures, this qualitative descriptive study analyzes 31 disease-related terms extracted from the Glossary of Medicine, Technology, and Sport (2025). The findings reveal that source-oriented procedures dominate the dataset, with Naturalization emerging as the most frequently applied strategy, followed by Transference, while Functional Equivalent is employed for terms with well-established vernacular counterparts. Through-Translation and Couplets occur less frequently and are primarily used to preserve the structural and semantic integrity of complex medical expressions. The findings further indicate that the selection of translation procedures is closely related to the presence or absence of target-language equivalents. While glossary translation generally prioritizes terminological consistency and scientific precision, target-oriented procedures are selectively employed to improve reader accessibility when culturally familiar expressions already exist. These findings contribute to translation studies by demonstrating how translators balance standardized medical terminology with reader comprehension in glossary-based translation and provide practical insights for translators and glossary compilers working with specialized medical terminology.